2013
DOI: 10.1007/s00787-013-0409-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of schizotypal symptoms following psychiatric disorders in childhood or adolescence

Abstract: It was examined how juvenile psychiatric disorders and adult schizotypal symptoms are associated. 731 patients of the Department of Child and Adolescent Psychiatry of the University Medical Centre Utrecht, the Netherlands, with mean age of 12.1 years (SD = 4.0) were reassessed at the mean age of 27.9 years (SD = 5.7) for adult schizotypal symptoms using the Schizotypal Personality Questionnaire-Revised (Vollema, Schizophr Bull 26(3):565-575, 2000). Differences between 13 juvenile DSM categories and normal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…In addition, unique associations emerged between positive schizotypy and 22q11DS-psychosis, and between negative schizotypy and ASD. These findings are consistent with psychometric studies showing common but also distinct relationships of positive and negative schizotypy with subclinical and clinical symptoms of neurodevelopmental conditions 9,10,1417 . An ADHD diagnosis during adolescence was found to predict higher total and negative schizotypy later in life 14 , and associations between higher ADHD features and positive schizotypy have been observed in relatives of individuals with schizophrenia 72,73 and in healthy individuals 74,75 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, unique associations emerged between positive schizotypy and 22q11DS-psychosis, and between negative schizotypy and ASD. These findings are consistent with psychometric studies showing common but also distinct relationships of positive and negative schizotypy with subclinical and clinical symptoms of neurodevelopmental conditions 9,10,1417 . An ADHD diagnosis during adolescence was found to predict higher total and negative schizotypy later in life 14 , and associations between higher ADHD features and positive schizotypy have been observed in relatives of individuals with schizophrenia 72,73 and in healthy individuals 74,75 .…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with psychometric studies showing common but also distinct relationships of positive and negative schizotypy with subclinical and clinical symptoms of neurodevelopmental conditions 9,10,14-17 . An ADHD diagnosis during adolescence was found to predict higher total and negative schizotypy later in life 14 , and associations between higher ADHD features and positive schizotypy have been observed in relatives of individuals with schizophrenia 72,73 and in healthy individuals 74,75 . Studies of 22q11DS individuals consistently reported elevated positive schizotypy scores 9,16,76 , mirroring the well-established increased risk of developing schizophrenia in this population 77 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Whether genetic markers associated with autism and psychosis are diametrical opposites remains open to debate. There is ample evidence, however, that etiological overlap between both conditions does exist, as further supported by recent studies focusing on polygenic risk for both autism and schizophrenia (Fromer et al, 2016 ; Pourcain et al, 2018 ; Velthorst et al, 2018 ), as well as the presence of rare copy-number variations in both populations (Kushima et al, 2018 ; Zarrei et al, 2019 ). In addition, given the highly heritable nature of both ASD and PD, it is reasonable to expect a higher co-occurrence of subclinical traits of both dimensions in unaffected relatives of either patient population.…”
Section: Introductionmentioning
confidence: 87%
“…Recent efforts have therefore focused more on dimensional rather than categorical approaches, under the assumption that both conditions represent extremes on a continuum of symptomatic severity, and that even isolated or low-intensity traits may affect clinical outcomes. Such studies have provided further evidence that autistic and psychotic traits co-occur at an elevated behavioral level in clinical samples (Barneveld et al, 2011;De Crescenzo et al, 2019;Esterberg, Trotman, Brasfield, Compton, & Walker, 2008;Fagel et al, 2013;Kincaid et al, 2017;Ziermans, Swaab, Stockmann, de Bruin, & van Rijn, 2017). From a cognitive and functional perspective, it is also well established that both ASD and PD are characterized by (partially) overlapping impairments compared to typical healthy comparisons, particularly in the social domain (Martinez et al, 2017;Pinkham et al, 2019;Sasson et al, 2007Sasson et al, , 2011Sasson et al, , 2016Velthorst et al, 2018).…”
Section: Introductionmentioning
confidence: 92%